Self-assembled aliphatic chain extended polyurethane nanobiohybrids: Emerging hemocompatible biomaterials for sustained drug delivery - Mishra A.; Singh S.K.; Dash D.; Aswal V.K.; Maiti B.; Misra M.; Maiti P. (My University, 2025)
Novel polyurethanes (PUs) have been synthesized using an aliphatic diisocyanate and aliphatic chain extenders with varying chain length. Nanocomposites of PUs have been prepared by dispersing 2-D nanoclay in poly-ol followed by prepolymerization and subsequent chain extension using various chain extenders. Systematic improvement in toughness and adequate enhancement in stiffness in the presence of nanoclay has been observed for PUs with longer chain extenders, and these new classes of nanocomposites exhibit no toughness-stiffness trade-off. Bottom-up self-assembly starting from the molecular level to micron-scale crystallite has been revealed through electronic structure calculation, X-ray diffraction, small-angle neutron scattering, atomic force microscopy and optical images. The role of hydrogen bonding has been revealed for this type of supramolecular assembly, and in the presence of organically modified nanoclay hydrogen bonding contributes to the formation of bigger clusters of nanocomposites. Controlled biodegradation of PU and its nanocomposites has been investigated in enzymatic media. Biocompatibility of these novel nanocomposites has been extensively verified through platelet adhesion, aggregation and hemolysis assay. Sustained drug delivery by biocompatible pristine PU and its nanocomposites has been demonstrated either by controlling the crystallite size of the polyurethane through alteration of the aliphatic chain length of the extender or by incorporating disc-like nanoclay, creating a tortuous path that results in delayed diffusion. Hence, the developed nanohybrids are potential biomaterials for tissue engineering and drug delivery. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.